IDENTIFICATION OF BRADYRHIZOBIUM JAPONICUM STRAIN ISOLATED FROM ROOT NODULES OF SHANKAPUSHPI (Clitorea ternatea L.) - P.DHANRAJ; A. P. MALLIKARJUNA GOWDA, R .MUTHURAJU; T.H. SHANKARAPPA; S. ANIL KUMAR; Y.S. PRANEETH; M. AVINASH (The Bioscan, 2020)
The study was under taken to isolate native strain of Rhizobium from Clitoria ternatea L. Known as shankapushpi, cultivated at College of Horticulture, Bengaluru. Rhizobium has been identified by following 16S rRNA analysis procedure. The objective of this study was to isolate and identify native strains of Rhizobium in shankapushpi root nodules on YEMA media and characterized for morphological properties. Partial 16S rRNA gene sequence from the isolates was amplified by PCR using 27F and 1492R primers. Purification and sequencing of the amplified fragments were done at macrogen laboratory Bengaluru. Sequences were analyzed using the programmed BLAST and results of BLAST queries showed that, the isolates have scored the maximum score, 100% query coverage, E value of 0.0 and 100% identity were selected as the probable identities of the isolate. Results of present study confirmed that, the presence of Bradyrhizobium japonicum strain in root nodules of Shankapushpi and deposited in the NCBI Gene Bank database under a unique accession number (KY864921). Identified strain from shankapushpi is of great importance because the symbiosis relationship between rhizobia and legumes is one of the effective agronomic practice to ensure an adequate supply of nitrogen for legumes, while improving fertility status of soils.